(untitled) (Journal of Nobel Medical College, 2018)
Introduction: Abnormalities in serum lipid and lipoprotein levels are recognized as major modifiable risk factors for cardiovascular disease and essential hypertension and retinopathy. So this study was conducted to evaluate the role of dyslipidemia on development of retinopathy in hypertensive patients and to establish the association of parameters of serum lipid profile with hypertensive retinopathy. Materials and Methods: A cross-sectional study was conducted in Ophthalmology Department among 135 patients in Nobel Medical College and Teaching Hospital (NoMCTH), Biratnagar who were diagnosed with essential hypertension. Patients having diabetes mellitus, myopia, hazy ocular media and other posterior segment disorders were excluded from the study. The detailed ophthalmic examination was carried out in department of ophthalmology, NoMCTH, Biratnagar and all the study population were investigated for fasting serum lipid profile. Result: Out of 135 patients with essential hypertension, 65.44% had retinopathy and remaining had no signs of retinopathy. Mean age of patients were 60.24 (±15.14) years. Although no gender preponderance was found with retinopathy but this study showed that hypertensive retinopathy increases significantly with increase in age and its incidence increases after the age of 60 years. Conclusion: The duration of hypertension was found to be strongly associated with development of hypertensive retinopathy. The increase in all the lipid profile parameters (Serum TG, TC, and LDL and LDL:HDL) and the obesity were found to be strongly associated with retinopathy in hypertensive patients.